2017
DOI: 10.5815/ijitcs.2017.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Time Concept Modeling for Querying Temporal Information in OWL and RDF

Abstract: Abstract-Ontology is an important factor in the integration of heterogeneous semantic information. Description logic, as a formal language for expressing ontologies, does not include the necessary features to create a temporal dimension in the relationships among concepts. It is critical to introduce time concepts to model temporal data and relate them to other non-temporal data recorded in ontology. Current query languages in the semantic web are not able to respond to temporal questions; thus, another import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…As one of the results of these limitations, the literature does not present examples of real case applications of these approaches, but only restricted studies based on temporal language queries, such as TOQL and SQWRL, as demonstrated by Bahadorani and Zaeri [29]. Section 4 lists the requirements of our approach aimed at covering these limitations.…”
Section: Comparison Of Approachesmentioning
confidence: 99%
“…As one of the results of these limitations, the literature does not present examples of real case applications of these approaches, but only restricted studies based on temporal language queries, such as TOQL and SQWRL, as demonstrated by Bahadorani and Zaeri [29]. Section 4 lists the requirements of our approach aimed at covering these limitations.…”
Section: Comparison Of Approachesmentioning
confidence: 99%
“…Numerous applications and ontologies have been developed based on the temporal models with the objectives of incorporating time into RDF and OWL structures. After defining time, is understanding and knowing how to process the stored information based on temporal models and then selecting an appropriate language to query and extract new knowledge from the knowledge base [12].…”
Section: A Data Warehousementioning
confidence: 99%